2008
DOI: 10.1016/j.neuroscience.2008.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Error-specific medial cortical and subcortical activity during the stop signal task: A functional magnetic resonance imaging study

Abstract: The ability to detect errors and adjust behavior accordingly is essential for maneuvering in an uncertain environment. Errors are particularly prone to occur when multiple, conflicting responses are registered in a situation that requires flexible behavioral outputs. Previous studies have provided evidence indicating the importance of the medial cortical brain regions including the cingulate cortex in processing conflicting information. However, conflicting situations can be successfully resolved, or lead to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
100
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(113 citation statements)
references
References 71 publications
11
100
2
Order By: Relevance
“…Errors are typically considered as rare, negative and interfering events, which need to be avoided, and can even activate the defensive/aversive motivational system (Hajcak & Foti, 2008). Accordingly, it is plausible that errors do not only influence cognitive mechanisms such as learning, attention, and memory, but also modulate affective states in order to promote adaptive and flexible behaviors (Hajcak et al, 2005;Li et al, 2008). Nevertheless, very few studies have corroborated this assumption so far (see Brazdil et al, 2002), and the impact of errors on brain systems implicated in emotional appraisal remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Errors are typically considered as rare, negative and interfering events, which need to be avoided, and can even activate the defensive/aversive motivational system (Hajcak & Foti, 2008). Accordingly, it is plausible that errors do not only influence cognitive mechanisms such as learning, attention, and memory, but also modulate affective states in order to promote adaptive and flexible behaviors (Hajcak et al, 2005;Li et al, 2008). Nevertheless, very few studies have corroborated this assumption so far (see Brazdil et al, 2002), and the impact of errors on brain systems implicated in emotional appraisal remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, very few studies have corroborated this assumption so far (see Brazdil et al, 2002), and the impact of errors on brain systems implicated in emotional appraisal remains largely unknown. Some preliminary evidence comes from functional neuroimaging studies that reported activations to errors in regions usually associated with emotional processing such as the amygdala or insula (Menon et al, 2001;Garavan et al, 2002;Polli et al, 2008Polli et al, , 2009Li et al, 2008). However, these studies do not inform about the exact time-course of error processing, in particular in relation to successive stages of motor preparation, execution, and/or feedback signals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a simple reaction time task in this stop signal paradigm (39,40,(63)(64)(65). There were two trial types, "go" and "stop," randomly intermixed.…”
Section: Methodsmentioning
confidence: 99%